2013
DOI: 10.1017/jsc.2013.31
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and analysis of data reduction techniques for the CReSS smoking topography device

Abstract: I ntroduction: Characterising smoking behaviour in an objective and ecologically valid manner is integral to understanding health complications associated with tobacco use. Smoking topography (ST) provides a representation of the physical attributes of smoking. However, there is no clear guidance on ST data exclusion and reduction techniques and the impact of different techniques. Methods: A search was conducted using MEDLINE, PubMed, and Scopus and limited to studies published between 2001-2012. The search id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…However, no manual for EC use was provided by the company. Previously, the CReSS Pocket has been used to study conventional cigarette topography [ 21 ]. Its adaption for use with EC topography is new, and 4–5 months were required to learn how to operate the CReSS Pocket reliably with EC users.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no manual for EC use was provided by the company. Previously, the CReSS Pocket has been used to study conventional cigarette topography [ 21 ]. Its adaption for use with EC topography is new, and 4–5 months were required to learn how to operate the CReSS Pocket reliably with EC users.…”
Section: Methodsmentioning
confidence: 99%
“…While conventional cigarette topography has been well documented [ 21 ], relatively little is known about the topography of EC users [ 22 ]. In data mined from YouTube videos, the average puff duration for EC users was 4.3 seconds, which is nearly twice the duration of conventional smokers [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing the number of relapses is of great interest to the community of tobaccorelated researchers. Many studies [2]- [5] have been conducted in an attempt to both properly describe smoking behavior as well as pinpointing the best-times to intervene such that a relapse does not occur. However, these studies are inherently limited due to the current methods of studying smoking behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies conducted rely on participants to self-report their smoking behavior. In various studies [2], [6], [7], the accuracy of self-reporting has been shown to be no more than ~76%. To bypass the reliance on self-reporting, some studies have been conducted in laboratory-based settings.…”
Section: Introductionmentioning
confidence: 99%